Effect of hot dip galvanization on the fatigue strength of steel bolted connections - S.M.J. Razavi; M. Peron; J. Torgersen; F. Berto; F. Mutignani (Fracture and Structural Integrity)
Hot dip galvanized steel bolted joints has been tested under fatigue loading to evaluate the effect of galvanizing coating on the fatigue strength of S355 structural steel. The experimental results showed that the decrease of the fatigue life of coated specimens in comparison with that of uncoated joints is very limited and the results are in good agreement with Eurocode detail category, without substantial reductions. The procedure for coating and preparation of the bolted joints is described in detail in this paper providing a useful tool for engineers involved in similar practical applications. The experimental results are compared with the previously published data on central hole notched galvanized and not treated specimens characterized by the same geometry.